Multidecadal Geomorphic Evolution of a Profoundly Disturbed Gravel Bed River System—A Complex, Nonlinear Response and Its Impact on Sediment Delivery. Issue 5 (27th May 2019) - Major, J. J.; Zheng, S.; Mosbrucker, A. R.; Spicer, K. R.; Christianson, T.; Thorne, C. R.
Abstract: A 2.5‐km 3 debris avalanche during the 1980 eruption of Mount St. Helens buried upper North Fork Toutle River valley and reset the fluvial landscape. Since then, a new drainage network has evolved. Cross‐sectional surveys repeated over nearly 40 years at 16 locations along a 20‐km reach of river valley document channel evolution. We analyze spatial and temporal changes in channel morphology using two new metrics: (1) a shape index that defines the degree of U‐shaped or V‐shaped valley geometry and (2) an alluvial phase space diagram that relates bed degradation or aggradation to increases or decreases in cross‐sectional area. Unlike a simple, linear response model previously proposed, our analysis reveals channel development has been distinctly nonlinear and nonsequential. Rather than following a sequential trajectory of (1) channel initiation and incision, (2) aggradation and widening, and (3) episodic scour and fill with little change in bed elevation, long‐term channel evolution has been more complex with vertical and lateral adjustments intertwined throughout. Our analysis reveals channel evolution has followed a complex trajectory that has migrated nonsequentially through several phase space domains including degradation and aggradation with widening and narrowing, bed‐level fluctuations with little change in cross‐section area, and changes in cross‐sectional area with little change of bed elevation. Persistent channel widening and reworking of the channel bed are responsible for maintaining elevated sediment delivery from this basin. Elevated sediment delivery is likely to persist until valley floor widths greatly exceed that of the channel migration zone, and/or channel slopes and valley walls stabilize. Plain Language Summary: A huge landslide filled upper North Fork Toutle River valley during the 1980 eruption of Mount St. Helens, Washington, and obliterated the existing landscape. Since then, the river has carved a new channel. We analyzed repeated surveys of channel cross sections at fixed locations to understand how channel shape has evolved and how that evolution controls sediment delivery from the basin. We developed two new ways of assessing changes in channel shape: (1) a shape index that defines whether the channel corridor is "U"‐ or "V"‐shaped, and (2) a diagram that relates channel bed scour and fill to increases or decreases in the cross‐sectional area of the slice of valley surveyed. We found that channel evolution has been more complicated than forecast after the eruption using simple ideas about channel initiation, bed scour, and channel filling and widening. Instead, changes in channel shape have involved different combinations of bed scour and fill with both channel widening and narrowing in a much more complex history. Persistent channel widening presently drives elevated sediment delivery from this basin compared to pre‐eruption conditions, and so high sediment loads are likely to continue for the foreseeable future. Key Points: A massive volcanic landslide reset the fluvial landscape of upper North Fork Toutle River A new alluvial phase space diagram describes a complex, nonlinear history of channel formation and evolution Lateral channel erosion is an important postdisturbance geomorphic process, and it drives persistent abnormally high sediment delivery